RESEARCHES ON DEVELOPMENT GRAIN GRINDER-CRUSHER FOR FARMERS AND PEASANTRY FARMS - Kholdarova Gulsanam Akramjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
In Uzbekistan the cattle is being fed by privet or peasantry farms, farmers and other types of agricultural organizations. There is no any grain grinder for farmers who have a few numbers of the cattle. Therefore, the small grain grinder-crusher was developed for them. It was defined that the grinding efficiency the corncob by the grinder-crusher was 99,2 per cent, crushing efficiency was 98,1 per cent, work efficiency was 130,4 kg/hour, expenditure of energy organized average 2,8 kW. And the grinding efficiency the grain of corn made up 99,6 per cent, crushing efficiency was 98,4 per cent, work efficiency in real work period constituted 172,5 kg/hour, expenditure of energy was average 3,6 kW. As if this situation was defined while grinding the grain of wheat and burley. It can be seen that, the work efficiencies increase considerably when the grain is ground than the corncob is ground, but together with this, the expenditure of energy rises to 28 per cent.